Tea you at the altar ebook - Thorne, Rebecca (Tomes & Tea, 2025)
The Princess Bride meets Bookshops and Bonedust in the third book of the Tomes & Tea series, where our favorite lesbian pirates must navigate the ultimate maelstrom—their own wedding! Kianthe and Reyna are ready to finally walk down the aisle—in just seven days, their wedding of a wifetime will be a reality. There's loads to do—but like all best laid plans, everything seems to be going awry. Between their baby dragons causing mayhem in Tawney, Kianthe's uptight parents inviting themselves to the wedding, and Reyna becoming embroiled in a secret plot to overthrow Queen Tilaine, the world seems against them—how are they going to live long enough to say "I do"? At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.